Study on Surface Roughness and True Fracture Energy of Recycled Aggregate Concrete Using Fringe Projection Technology - Meiling Dai; Weiyi Hu; Chengge Hu; Xirui Wang; Jiyu Deng; Jincai Chen (Fractal and Fractional)
This paper investigates the fracture surfaces and fracture performance of recycled aggregate concrete (RAC) using fringe projection technology. This non-contact, point-by-point, and full-field scanning technique allows precise measurement of RAC’s fracture surface characteristics. This research focuses on the effects of recycled aggregate replacement rate, water-to-binder (w/b) ratio, and maximum aggregate size on RAC’s fracture properties. A decrease in the w/b ratio significantly reduces surface roughness (Rs) and fractal dimension (D), due to increased cement mortar bond strength at lower w/b ratios, causing cracks to propagate through aggregates and resulting in smoother fracture surfaces. At higher w/b ratios (0.8 and 0.6), both surface roughness and fractal dimension decrease as the recycled aggregate replacement rate increases. At a w/b ratio of 0.4, these parameters are not significantly affected by the replacement rate, indicating stronger cement mortar. Larger aggregates result in slightly higher surface roughness compared to smaller aggregates, due to more pronounced interface changes. True fracture energy is consistently lower than nominal fracture energy, with the difference increasing with higher recycled aggregate replacement rates and larger aggregate sizes. It increases as the w/b ratio decreases. These findings provide a scientific basis for optimizing RAC mix design, enhancing its fracture performance and supporting its practical engineering applications.